2007
DOI: 10.1243/09576509jpe332
|View full text |Cite
|
Sign up to set email alerts
|

Tidal energy resource assessment for tidal stream generators

Abstract: This article is a review of the current understanding of tidal energy resources in the context of the emerging technology of tidal stream power generation. The geographical focus is on the north-west European continental shelf, the scope of a number of published reports on exploitable tidal stream energy resources. These estimates are reviewed as are some analytical models of energy extraction by tidal stream generators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 34 publications
2
62
0
Order By: Relevance
“…Albert Betz (1885 -1968), a German Physicist, showed that the maximum theoretical power coefficient for any turbine (assuming the rotor is frictionless and has no rotational velocity component in the wake) operating in a free stream flow is 0.59. This is known as the Betz limit [24]. However, the presence of an upper and lower boundary (the surface and the seafloor) may result in an increase in the maximum theoretical power coefficient if the turbine occupies a large portion of the flow channel [21].…”
Section: Theoretical Tidal Current Energy Resourcementioning
confidence: 99%
“…Albert Betz (1885 -1968), a German Physicist, showed that the maximum theoretical power coefficient for any turbine (assuming the rotor is frictionless and has no rotational velocity component in the wake) operating in a free stream flow is 0.59. This is known as the Betz limit [24]. However, the presence of an upper and lower boundary (the surface and the seafloor) may result in an increase in the maximum theoretical power coefficient if the turbine occupies a large portion of the flow channel [21].…”
Section: Theoretical Tidal Current Energy Resourcementioning
confidence: 99%
“…where V cutin , V rated , P rated are the cut-in speed, rated speed and rated power of the TPGS, respectively; C p the power capture coefficient and its value for a typical design is in the range of 0.4*0.5 [18]; q the seawater density; A the area swept out by the tidal turbine rotor; and V t the tidal current speed. According to (3), a TPGS starts to deliver electric power when the tidal current speed exceeds the cut-in speed and reaches its rated power (P rated ) when the tidal current speed is at V rated .…”
Section: Power Output Model Of Tpgsmentioning
confidence: 99%
“…Note that the load curtailments are calculated in different combinations of events when the WPGS is in service and out-ofservice and when the BESS is available and unavailable. The loss of load expectation index (LOLE) is defined as the expected duration within a certain period of time (such as 1 year) over which the load demand exceeds the total generated power [18]. Mathematically, the LOLE (I LOLE ) for the model presented in the paper can be expressed by: …”
Section: Loss Of Load Expectation Indexmentioning
confidence: 99%
“…C p = C p (λ, β) is a function of the blade pitch angle β and the tip speed ratio λ. Betz's law states that the maximum amount of energy extracted by the device is C p < 0.59 [12,30]. A theoretical power coefficient, C p , of 0.45 was assumed for the tidal turbines, following the analysis in [31]. However, the actual power coefficient is, in fact, less than that due to the parameterisation of the turbine power curves, as shown in The simulation model of the turbines and power distribution is based on the following hypothesis:…”
Section: Turbine Modellingmentioning
confidence: 99%